2020
DOI: 10.1016/j.apsusc.2019.144473
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of supported Au-Pd nanoparticles on synthesized CeO2 with different morphologies and application in solvent-free benzyl alcohol oxidation

Abstract: Shusen 2020. Investigations of supported Au-Pd nanoparticles on synthesized CeO2 with different morphologies and application in solvent-free benzyl alcohol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The corresponding results were summarized in Table S1 in SI, which demonstrated that >96% of Au and Pd were successfully anchored on the catalyst surface. The difference between the nominal and actual metal concentration might be attributed to the measurement deviation and the leaching of the weakly adsorbed AuPd during the catalyst preparation [30].…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding results were summarized in Table S1 in SI, which demonstrated that >96% of Au and Pd were successfully anchored on the catalyst surface. The difference between the nominal and actual metal concentration might be attributed to the measurement deviation and the leaching of the weakly adsorbed AuPd during the catalyst preparation [30].…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Liu et al, AuPd/CeO 2 with 1.2 wt % metal loading and Au:Pd = 1:5 exhibited extremely high activity with a TOF = 30.1 s –1 at 160 °C due to the optimized noble metal nanoparticle distribution and the ceria support with high Ce 3+ content and abundant oxygen defects . Similar to the CeO 2 -supported Au catalyst, the morphology, structure, and physicochemical properties of CeO 2 would also affect the catalytic activity of Au-Pd NPs/CeO 2 in selective oxidation . Au-Pd supported on CeO 2 nanorods was demonstrated to exhibit higher catalytic activity (TOF > 35 900 h –1 ) than Au-Pd supported on conventional CeO 2 due to the high concentrations of oxygen vacancies and Ce 3+ in CeO 2 nanorods as well as the small size of the Au-Pd nanoparticles …”
Section: Ceria-based Catalysts For Selective Oxidation Via Thermocata...mentioning
confidence: 99%
“…Up to now, the design and synthesis of supported bimetallic catalysts with positive synergetic effects have attracted substantial attention in the catalytic fields, such as organic transformations, CO oxidation, and VOCs decomposition . To increase the catalytic activity of Au nanoparticles in alcohol oxidation to the corresponding aldehydes, introducing other metal elements (e.g., Pd, Ce–Al) to form alloys with Au provides another strategy . For example, Hutchings et al prepared CeO 2 by an antisolvent precipitation technique using supercritical CO 2 (i.e., scCeO 2 ) as support of 2.5 wt %Au-2.5 wt %Pd catalysts for the solvent-free selective oxidation of alcohols using O 2 as oxidant, and the as-prepared 2.5 wt %Au-2.5 wt %Pd/scCeO 2 catalyst with intimately mixed and uniformly highly dispersed surface Au 0 and Pd 2+ species exhibited higher activity than scCeO 2 -supported catalysts containing monometallic Au and Pd only .…”
Section: Ceria-based Catalysts For Selective Oxidation Via Thermocata...mentioning
confidence: 99%
“…Shape-selective synthesis of inorganic nanomaterials is of scientific and technological importance because of their unique shape-dependent material properties. The morphological effect on the overall functionality of CeO 2 explains the importance of their shape-controlled synthetic strategy. Experimental and theoretical studies have confirmed that some CeO 2 nanocrystal properties are surface-structure-dependent .…”
Section: Introductionmentioning
confidence: 99%